Recent Advances in Bioconjugate Vaccine Development - Brendan W. Wren; Catherine L. Hall; Vanessa S. Terra; Mark A. Harrison; Elizabeth Atkins; Fauzy Nasher; Ian J. Passmore (Vaccines)
Glycoconjugate vaccines, consisting of a protein component covalently linked to a glycan antigen, have led to a significant reduction in the global occurrence of bacterial meningitis and pneumonia. They provide robust, lasting immunity in all age groups. However, their production by traditional chemical conjugation approaches has drawbacks in terms of complexity, cost, and lack of flexibility in design, which explains their limited application to a few pathogenic bacteria in the past four decades. Protein glycan coupling technology (PGCT) or bioconjugation, where glycoconjugates are produced in purpose-engineered bacterial cells, is a useful alternative to chemical conjugation and promises an array of low-cost custom-made glycoconjugate vaccines with vast protein glycan combinations. The technology has undergone significant development since its inception, and new advances and refinements continually drive the field forward. Several bioconjugate vaccines are currently in clinical trials, demonstrating the potential of the technology. We will review the wide applicability of bioconjugation and recent developments in each of the components of the technology, namely, glycan expression, protein selection, and the coupling of selected glycan with proteins, all within custom-designed E. coli cells. These advances promise to deliver effective glycoconjugate vaccines for multiple unmet medical needs.